Telehealth memory clinics in primary healthcare: real-world experiences from low-resource settings in Greece - Aggeletaki, Eleutheria; Stamos, Vasileios; Konidari, Eleni; Efkarpidis, Apostolos; Petrou, Anna; Savvopoulou, Kalliopi; Kontogianni, Evangelia; Tsimpanis, Konstantinos; Vorvolakos, Theofanis; Politis, Antonios; Alexopoulos, Panagiotis (Frontiers in Dementia, 2024)
The role of primary healthcare is pivotal in the management of the surge of dementia prevalence particularly in low-resource areas. Here, two telehealth-based memory clinics in primary healthcare operating within the frames of the INTegRated InterveNtion of pSychogerIatric Care (INTRINSIC) are presented.The first clinic, which is led by a general practitioner, operates at a primary healthcare center in a semi-mountainous area and closely collaborates with the geriatric psychiatry outpatient clinic of the Patras University General Hospital via a telehealth medicine platform. The second clinic is embedded at the General Hospital Center for Interconnected Psychiatric Support in the island of Syros, is led by registered nurses and is interconnected with the old-age psychiatry unit at the Eginition University Hospital in Athens.Results: Both memory clinics are in their infancy. At the general practitioner-led memory clinic 13 beneficiaries were assessed and treated during the first six months of its operation. Cognitive decline and depressive and/or anxiety symptoms were detected in ten and eight individuals, respectively. In nine of the 27 beneficiaries of the registered nurse-led memory clinic either mild cognitive impairment or dementia was diagnosed, while affective and/or anxiety symptoms were detected in almost all of them. Of note, only 14 beneficiaries of both clinics had received a diagnosis of a mental or neurocognitive disorder prior their assessment at the memory clinics.Developing memory clinics in primary healthcare may be a pragmatic strategy to improve access of older adults living in low-resource areas to cognitive healthcare services.